Restrictive relative clauses in Greek Heritage speakers in the US - Alexiadou, Artemis; Rizou, Vasiliki (Bergen Language and Linguistics Studies, 2022)
This paper investigates the production of restrictive relative clauses (henceforth RRCs) in Heritage Greek in contact with US English. In Greek, RRCS are introduced either by the pronoun o opios ‘the who’ which agrees with the nominal head it modifies and is preferred in formal registers; or by the un-inflected complementizer pu 'that', which appears mostly in colloquial speech. In English, RRCs are introduced by the non-agreeing pronouns who and which and by the complementizer that. The findings suggest that both groups favour the production of pu RRCs but we cannot attribute the overuse of pu RRCs by HSs to English interference. There is no clear evidence that o opios is preferred in formal registers by monolinguals and we argue that HSs avoid o opios RRCs as they have difficulties with establishing agreement between nouns and modifiers. This is corroborated by their use of the English non-agreeing pronouns who and which.